2007
DOI: 10.3168/jds.2006-445
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Paraoxonase, Health, Inflammatory Conditions, and Liver Function in Transition Dairy Cows

Abstract: Paraoxonase (PON) is a liver protein with hydrolase activity that is released into the blood stream. Paraoxonase may serve as an index of liver function because it is drastically reduced in chronic liver damage. Sixty-seven periparturient dairy cows were used to evaluate the relationship between plasma PON, health problems, inflammatory conditions, and liver function. Baseline plasma PON concentrations during the first 30 d in milk (DIM) were retrospectively used to group cows into quartiles. Metabolic profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
369
11
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 367 publications
(422 citation statements)
references
References 19 publications
39
369
11
3
Order By: Relevance
“…haptoglobin, ceruloplasmin, serum amyloid A) while, at the same time, it starts the decrease of common liver proteins (i.e. albumin, lipoprotein, retinol binding protein, cortisol binding globulin, PON) which are referred to as negative acute phase proteins (Gruys et al, 2005;Bionaz et al, 2007). In our study we observed a higher concentration of ceruloplasmin and a lower concentration of PON and cholesterol before parturition, which seems to support the presence of inflammatory conditions in the prepartum rabbit females.…”
Section: Effect Of Transition Period In Reproductive Rabbit Doessupporting
confidence: 79%
See 2 more Smart Citations
“…haptoglobin, ceruloplasmin, serum amyloid A) while, at the same time, it starts the decrease of common liver proteins (i.e. albumin, lipoprotein, retinol binding protein, cortisol binding globulin, PON) which are referred to as negative acute phase proteins (Gruys et al, 2005;Bionaz et al, 2007). In our study we observed a higher concentration of ceruloplasmin and a lower concentration of PON and cholesterol before parturition, which seems to support the presence of inflammatory conditions in the prepartum rabbit females.…”
Section: Effect Of Transition Period In Reproductive Rabbit Doessupporting
confidence: 79%
“…Ions (K and Cl) were measured by the potentiometer method (ion-selective electrode connected to ILAB 650). Zn, NEFA and BHBA, were measured by the methods previously reported (Bionaz et al, 2007). Haptoglobin and ceruloplasmin were analysed using methods described in Skinner et al (1991) and Sunderman and Nomoto (1970), respectively, adapted to the ILAB 650 conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, the cow is unable to meet these energetic requirements (Taylor et al, 2003) and this results in negative energy balance (NEBAL) that begins few days before calving and usually reaches its nadir about 2 weeks later (Butler and Smith, 1989;Bell, 1995). In such a forced metabolic condition, an increase in reactive oxygen species (ROS) generation may occur and, subsequently, oxidative stress may develop (Miller et al, 1993;Mudron et al, 1999;Bionaz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the cow is unable to meet these energetic requirements (Taylor et al, 2003) and this results in negative energy balance (NEBAL) that begins few days before calving and usually reaches its nadir about 2 weeks later (Butler and Smith, 1989;Bell, 1995). In such a forced metabolic condition, an increase in reactive oxygen species (ROS) generation may occur and, subsequently, oxidative stress may develop (Miller et al, 1993;Mudron et al, 1999;Bionaz et al, 2007).- E-mail: r.sciorsci@veterinaria.uniba.it 118 In physiologic conditions, living organisms have sophisticated antioxidant defence systems, both enzymatic and non-enzymatic, to counteract excessive ROS levels (Takata et al, 2002;Locher et al, 2011). Among non-enzymatic antioxidants, a-tocopherol (a-toc) and carotenoids need to be mentioned (Lindmark-Mansson and Akesson, 2000;Havemose et al, 2004).…”
mentioning
confidence: 99%